Guest commentary:takaful-development and challenges over 20 years of its existence in Malaysia - Kamaruddin Sharif (Penerbit Universiti Kebangsaan Malaysia, 2004)
Even though the fundamentals of takaful were laid centuries ago, its modern form only appeared in the last twenty five years. Its growth had been remarkable especially in Malaysia. Despite of the impressive growth rate, its penetration rate compared to that of insurance is still minimal.Being a relatively recent phenomenon, takaful operators need to provide a cediable, effective, efficient and significant alternative against conventional insurers.In order to be more relevant in the marketplace, they need to increase the awareness of the masses, relook at their present distribution channel, keep abreast with the latest technologies, introduce new appopriate products and reposition themselves more as a risk management advocator and these need to be done in earnest and immediately